Sustainability in the university curriculum in biological and agricultural sciences - Viveros Contreras, Rodolfo; Serrano Solis, Arturo; Landero Hernández, Lourdes (IE Revista de Investigación Educativa de la REDIECH, 2024)
In recent years, given the conditions of structural crisis that prevail in the society-environmental relationship, it has emerged as necessary and urgent to incorporate the environmental dimension into the university curriculum. Higher education institutions cannot be visualized today isolated from a sustainable approach that supports the formative and disciplinary demands of the field of professions. This study analyzes how the Sustainable Development Goals (SDGs) established in the 2030 Agenda are present in the degrees of the Universidad Veracruzana (UV) belonging to the biological-agricultural area. The objective was to identify to what extent in the curricula the attention to the SDGs is enunciated in the different approaches and training processes of university careers. To this end, from a methodology that contemplated mixed perspectives (quantitative and qualitative) and based on instruments adapted based on the existing literature, a tool was designed to analyze in the curriculum the elements of the SDGs and their formative implications in the objectives and competencies proposed in university careers.